Legal Vacuity Regarding Legal Protection for Victims of Criminal Acts of Defamation in Electronic Media - Wieke Dewi Suryandari (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the legal gap in legal protection for victims of criminal acts of defamation in electronic media and the challenges and efforts to protect them. Although the Electronic Information and Transactions Law (UU ITE) has regulated criminal acts of libel, there is still a legal gap in terms of victim protection, especially in enforcing victims' rights and resolving cases through clear legal mechanisms. This study uses a normative legal research method with a legislative approach and a conceptual approach to explore existing legal regulations and analyze the challenges in their implementation practices. The study results indicate that the lack of clarity in the definition and application of the law between the Criminal Code and the ITE Law confuses perpetrators and victims in accessing justice. Therefore, this study proposes the need for legal harmonization, as well as strengthening the legal protection mechanism for victims through clearer regulations and consistent application.